High-resolution helium ion microscopy of epididymal epithelial cells and their interaction with spermatozoa - Păunescu, Teodor G. (Oxford University Press, 2014)
We examined the rat and mouse epididymis using helium ion microscopy (HIM), a novel imaging technology that uses a scanning beam of He(+) ions to produce nanometer resolution images of uncoated biological samples. Various tissue fixation, sectioning and dehydration methods were evaluated for their ability to preserve tissue architecture. The cauda epididymidis was luminally perfused in vivo to remove most spermatozoa and the apical surface of the epithelial lining was exposed. Fixed epididymis samples were then subjected to critical point drying (CPD) and HIM. Apical stereocilia in principal cells and smaller apical membrane extensions in clear cells were clearly distinguishable in both rat and mouse epididymis using this technology. After perfusion with an activating solution containing CPT-cAMP, a permeant analog of cAMP, clear cells exhibited an increase in the number and size of membrane ruffles or microplicae. In contrast, principal cells did not exhibit detectable structural modifications. High-resolution HIM imaging clearly showed the ultrastructure of residual sperm cells, including the presence of concentric rings on the midpiece, and of cytoplasmic droplets in some spermatozoa. Close epithelium–sperm interactions were also detected. We found a number of sperm cells whose heads were anchored within the epididymal epithelium. In certain cases, the surface of the sperm cytoplasmic droplet was covered with vesicle-like structures whose size is consistent with that of epididymosomes. In conclusion, we describe here the first application of HIM technology to the study of the structure and morphology of the rodent epididymis. HIM technology represents a major imaging breakthrough that can be successfully applied to study the epididymis and spermatozoa, with the goal of advancing our understanding of their structure and function.